Balance Scorecard As a Tools For Measuring The Performance of Government Institutions : A Literature Review - Sulthan Yusuf Abdullah; Illa Susilawati; Nadi Azkia Ali Alfathimi; Aristanti Widyaningsih; Denny Andriana (The International Journal of Business Review (The Jobs Review), 2022)
Balanced Scorecard (BSC) was introduced in the United States in the early 1990s and is used as a performance measure in future organizations and as a measurement tool in all institutions. This study aims to explain how the implementation of the balanced scorecard in government agencies in Indonesia in assessing its contribution to the accountability of their performance. This study uses the Systematic Literature Review (SLR) method by reviewing and reviewing several journal articles within a period of 5 years starting from 2017 to 2021. The results of this study indicate that the application of the Balanced Scorecard (BSC) in government institutions in Indonesia is used as a tool to measure performance and as information for improving employee performance has been successfully applied in all government sectors. The limitations of this study are the supporting references for research are still inadequate and the theories used have not been updated. This research is expected to add and update insights about the Balanced Scorecard (BSC) in government institutions.